2000
DOI: 10.1086/315768
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Virulence ofCandida albicansIsolates Causing Mucosal Infections in People Infected with the Human Immunodeficiency Virus

Abstract: Mucosal candidiasis is common in human immunodeficiency virus (HIV) infection. Susceptibility to such infections may be attributed to reduced host defense mechanisms and/or virulence of the organism. In the present study, we compared the virulence of mucosal Candida albicans isolates from HIV-infected people, with and without fluconazole-refractory infection, in established murine models of systemic and vaginal candidiasis. Compared with the mortality rate ( approximately 70%) after intravenous challenge with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 15 publications
2
28
0
1
Order By: Relevance
“…It is noteworthy that C. albicans strains vary considerably in their ability to colonize mucosal sites (44,58). The gene expression pattern exhibited by strains with enhanced ability to colonize may differ in interesting ways from the pattern of gene expression observed in this study.…”
Section: Discussionmentioning
confidence: 56%
“…It is noteworthy that C. albicans strains vary considerably in their ability to colonize mucosal sites (44,58). The gene expression pattern exhibited by strains with enhanced ability to colonize may differ in interesting ways from the pattern of gene expression observed in this study.…”
Section: Discussionmentioning
confidence: 56%
“…Candida colonization varies by both mucosal site and Candida species and strain (24,31). It is important to note that the differences between C. albicans strains are not well understood, and even Candida species show altered organ specificity during GI colonization, as demonstrated by Candida pintolopesii preferentially colonizing the murine stomach (2).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the interaction between the immune system and MDR transporters in C. al-bicans may also extend to transporters of the major facilitator superfamily, since deletion of the CaMDR1 gene in C. albicans has been shown to result in reduced virulence (7). Finally, other studies have shown that the virulence of C. albicans strains does not appear to be related to their azole resistance status (5,70), although the molecular mechanism of azole resistance in these strains was not identified. It will be important to determine the capacity of multidrug transporters to modulate C. albicans virulence in animal models by using wellcharacterized strains engineered to overexpress such transporters individually or in combination in otherwise identical genetic backgrounds.…”
Section: Vol 47 2003mentioning
confidence: 97%